Application Perspectives of Corpus-Based Methods Within Linguo-Cultural and Psycholinguistic Analysis: German Emotional Concept Sehnsucht - Mizin, Kostiantyn; Ovsiienko, Lesia (East European Journal of Psycholinguistics, 2020)
The paper aims at exploring the German emotional concept SEHNSUCHT features on the basis of corpus-based method being part of contrastive linguo-cultural (language-and-culture oriented) analysis of specific linguo-cultural (language-and-culture) concepts. The tested method includes two research procedures: 1) establishing relevant senses of the concept SEHNSUCHT and identifying their basic sense clusters by contrastive translation analysis of concordances built on the basis of the word query Sehnsucht; 2) determining the emotional concepts that can serve as the representatives of the concept SEHNSUCHT in the target linguo-cultures (languages and cultures). The latter procedure includes processing the co-occurrent profile of the word query Sehnsucht. This profile is an up-to-date definition of the lexeme Sehnsucht. By extrapolating the basic semantic features of this definition on the cognitive features of the concept SEHNSUCHT, the main concept representatives of the latter have been determined. It has been revealed that the basic emotional senses of the concept SEHNSUCHT (‘striving’, ‘desire’, ‘wish’, ‘longing’, ‘mourning for a person one loses’, ‘passionate attraction’ and others) create the following sense clusters: 1) ‘intensive inner affection’; 2) ‘passionate (sexual) affection’; 3) ‘striving for life changes (alternatives)’; 4) ‘longing (nostalgia) for life changes (alternatives)’; 5) ‘mourning (grief) for another person, often with no hope’. Based on the linguistic corpus statistic data as of the frequency of co-occurrent-like forms, co-occurrents and left- and right-hand collocates of the word query Sehnsucht, the co-occurrent profile of the word was developed. With the help of the relevant definition of the lexeme Sehnsucht studied on the basis of the co-occurrent profile, the basic concept representatives of the concept SEHNSUCHT, i.e. PASSION, DESIRE, SADNESS, were revealed. These concepts can facilitate an adequate transfer of the specific concept SEHNSUCHT to the target languages and cultures, provided no adequate analogue exists. The tested method may be also applied in psycholinguistic studies aimed at mental and verbal categorization of specific emotions.